Causality between money supply and price: evidence from Malaysia - Ismail, Maymunah; Abdamia, Noranita; Abu Bakar, Bazri (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2005)
From 1973 to 2004, Malaysia experienced unique inflation trends and allowed greater exchange rate flexibility, abandoning monetary targets in favor of interest rate targeting as the perceived usefulness of money as a predictor of inflation declined. This study hypothesizes that money supply is the cause and price is the effect in describing the inflation phenomenon in Malaysia. Investigating the causality between money supply and prices provides essential statistical insights for policy-making authorities. Consequently, this study aims to identify the important monetary aggregates that contribute significantly to inflation in Malaysia. The empirical results indicate that only M3 exhibits a long-run dynamic relationship and bi-directional causality with the price level.